Myśl narodnicka a polski ruch niepodległościowy. Powstanie styczniowe w prozie Nikołaja N. Złatowratskiego - Grącka, Monika (Acta Polono-Ruthenica, 2018)
The Narodnik current was in the 1870s the main trend of the Russian social thought. It has left long-lasting tracks in the philosophy, sociology, history and literature. The Narodnik ideology was being formed around the aspirations to create the just social system based on the equality and independency. The role of Russia, in the Narodniks’ conviction, was to begin the social changes guaranteeing justice, brotherhood and human dignity in the world. In the same time the Russia itself subjugated the Polish nation and suppressed effectively all Polish aspirations to regain independency. Thus the subject of the article is the characteristics of the Narodnik theoreticians’ stands on the January Uprising of the 1863 and also the analysis of the Nikolaj N. Zlatovratskij’s - the leading representant of the Narodnik current in Russian literature - chosen works to present the writer’s attitude to the Polish struggle for the national liberation.